FINITE ELEMENT METHOD STUDIES ON THE TRANSMISSION OF MASTICATORY FORCES TO THE BONE SUBSTRATE VIA TITANIUM AND ZIRCONIUM IMPLANTS - Sabina David; Ioan Sârbu; Raluca Monica Comăneanu; Dan Nicolae Pătroi (Amaltea Medical Publishing House, 2018)
In this study we compared the modalities of transmitting experimental masticatory forces through titanium or zirconium dental implants to the bone substrate. According on the finite element analysis, the biomechanical behavior of the zirconium implant is better than the biomechanical behavior of the titanium implant, because the zirconium implant, by its features, attenuates the transfer of stresses between it and the bone, keeping osteointegration.